Ice hockey and football in Norway: parallel lines, different levels - Jensen, C. T. (Sport in Society: Cultures, Commerce, Media, Politics, 2025)
By comparing the development of ice hockey and football in Norway from the beginning of the twentieth century until today, the study shows how structures within ice hockey and in Norwegian society have hindered the development of ice hockey and favoured that of football. Based on an analysis of local ice hockey clubs and press coverage, the paper shows that the sports followed a similar line of development in three phases albeit with very different outcomes. In the initial phase both sports founded a national federation and sought to expand. In the latter, football proved much more successful than ice hockey, whose equipment and facilities were costly. In the post-war phase, the study shows how football benefitted from the new national lottery money whereas ice hockey only got new facilities due to the 1952 Olympics, and as a temporary event, the Games did not prove a lasting source of support. Finally, in the most recent phase marked by professionalisation, both ice hockey and football were characterised by a high interest in professionalisation, but in particular for ice hockey clubs it was challenging to turn the sport into a sustainable business.